1998
DOI: 10.1093/annonc/9.suppl_5.s147
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life assessment in Hodgkin’s disease: A new comprehensive approach

Abstract: Previous reports from available trials have dealt with negative long-term sequelae in Hodgkin's disease (HD) survivors. There is, however, a lack of longitudinal data showing the correlation between outcome and various treatment-related variables and the process of re-adaptation into normal life after the end of treatment. In order to investigate the quality of life (QoL) of patients with HD in different dimensions during active treatment and follow-up and to identify longitudinal patterns of QoL dimensions du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…30,31 Studies in patients with Hodgkin's Lymphoma also show that physical and social areas are greatly affected. 32 As expected, age and time elapsed since the diagnosis are negatively associated with several facets of QOL, such as general health, emotional role, physical function, social function and the composed physical scale. A striking result is the negative association between educational level and pain.…”
Section: Discussionsupporting
confidence: 59%
“…30,31 Studies in patients with Hodgkin's Lymphoma also show that physical and social areas are greatly affected. 32 As expected, age and time elapsed since the diagnosis are negatively associated with several facets of QOL, such as general health, emotional role, physical function, social function and the composed physical scale. A striking result is the negative association between educational level and pain.…”
Section: Discussionsupporting
confidence: 59%
“…Oncologist ® Studies in patients with a range of cancer diagnoses have reported the expected negative correlation between the incidence of CRF and patients' QoL [7,36,[45][46][47][48]. In their study of fatigue, psychological distress, and functional status among women receiving radiotherapy for uterine cancer, Ahlberg and coworkers found highly statistically significant negative correlations between general fatigue and multiple domains of QoL, including physical, role, emotional, cognitive, and social functioning (all p < .001, except social functioning p = .002) [36].…”
Section: Thementioning
confidence: 99%
“…These include impaired memory and concentration, depression and anxiety, sexual problems, and problems with employment and insurances. 8,18,19 This review will focus on the risk of second malignancy and CVD after HL treatment, because these late effects contribute most to the substantial excess mortality after HL treatment. 1,2,5,20,21 Although HL is the major cause of excess death in the first 10 to 15 years after diagnosis, excess mortality after this period is mainly due to second malignancies and CVD.…”
Section: Introductionmentioning
confidence: 99%